Parental grief and photographic remembrance : a historical account of undying love - Hamer, Felicity T. C. (Emerald Publishing Limited, 2020)
Photographic portraits of those who have passed have the potential to become valuable sites of remembrance. Across North America and Western Europe, parents are increasingly unfamiliar with death; lacking the rituals and tools that have historically eased the bereavement process. This book shines a light on how semi-private social media groups enable the bereaved parents of today to navigate their grief in the modern world. The author explores how creative, and sometimes contested, incorporations of photography within these online spaces demonstrate a revival and renegotiation of historic practices. By shining a light on recurrent tendencies and their evolution within new media this book offers an opportunity to observe the complex relationships grief can prompt some individuals to form with the portraits of absent loved ones. As social networking sites continue to enable the reinsertion of death within the social realm, the author looks ahead: might we begin to see a revival and increased openness towards end-of-life, post-mortem and funerary photography? As bereavement increasingly becomes something communicated in an online context, what new types of embellishments to the photographic portrait might we encounter?
Includes index.
Keywords: Parental grief.; Social media -- Psychological aspects.; Postmortem photography.; Psychology, Grief & Loss.; Psychology: emotions.; elektronické knihy; electronic books